Phase equilibria, glass formation and optical properties of glasses in the Ag2S–BIVS2–CV2S3 systems (BIV–Ge, Sn; CV–As, Sb) - Berezniuk О.P.; Petrus’ , I.I.; Olekseyuk, I.D.; Zamuruyeva, O.V.; Skipalskiy, M.I. (Physics and Chemistry of Solid State, 2022)
Phase equilibria of the quasi-ternary systems Ag2S–BIVS2–CV2S3 (BIV– Ge, Sn; CV–As, Sb) were investigated using phase analysis based on XRD. Isothermal sections at 500 Kand glass formation regions in the respective systems were determined. The quasi-binary sections GeS2–As2S3 and GeS2–Sb2S3 of the studied systems exhibit glass formation in the entire concentration range. Large glass formation regions were also found at the Ag2S–GeS2 (0–55 mol.% Ag2S) and Ag2S–As2S3 (0–75 mol.% Ag2S) sections. As the starting compounds As2S3, GеS2 and Sb2S3 are in the glassy state, they act as the glass-forming agents in the quasi-ternary systems. Glass formation regions in the tin-containing systems are significantly smaller than the analogous germanium-containing ones which is due to metal nature resulting in the change from tetrahedral to octahedral surrounding. Glassy materials may possess interesting optical properties, therefore optical absorption spectra at 297 K were measured. Bandgap energy Eg of the glasses of the quasi-binary system GeS2–As2S3 was estimated from the data on the spectral distribution of the absorption coefficient at the fundamental absorption edge. It was found that the addition of As2S3 to germanium (IV) sulfide results in shifting the absorption edge to higher energies.